2015
DOI: 10.1111/ejn.13041
|View full text |Cite
|
Sign up to set email alerts
|

Hold your pauses: external globus pallidus neurons respond to behavioural events by decreasing pause activity

Abstract: Awareness of its rich structural pathways has earned the external segment of the globus pallidus (GPe) recognition as a central figure within the basal ganglia circuitry. Interestingly, GPe neurons are uniquely identified by the presence of prominent pauses interspersed among a high-frequency discharge rate of 50-80 spikes/s. These pauses have an average pause duration of 620 ms with a frequency of 13/min, yielding an average pause activity (probability of a GPe neuron being in a pause) of (620 × 13)/(60 × 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The increase in neuronal activity at the population level after cues occur is consistent with previous findings (Deffains et al, 2016;Noblejas et al, 2015). Noblejas and colleagues have shown that the average GPe activity increases in response to relevant behavioral events.…”
Section: Gpe Neurons Are Strongly Modulated By Reward Size But Only supporting
confidence: 90%
“…The increase in neuronal activity at the population level after cues occur is consistent with previous findings (Deffains et al, 2016;Noblejas et al, 2015). Noblejas and colleagues have shown that the average GPe activity increases in response to relevant behavioral events.…”
Section: Gpe Neurons Are Strongly Modulated By Reward Size But Only supporting
confidence: 90%
“…Interestingly, in humans, ethanol appears to decrease GPe activity, as evidenced by neuroimaging studies in which an oral dose of ethanol dampened the increase of GPe activity during a visual task and induced a slight decrease of GPe activity (Nikolaou et al , 2013). Although we are aware that GPe high-frequency neurons are characterized by interspersed pauses in monkeys (DeLong, 1971; Elias et al , 2007; Noblejas et al , 2015; Schechtman et al , 2015), we observed only occasional pausing behavior in some GPe neurons (data not shown). One reason for this difference may be species, as in rodents it has been reported that a subset of high-frequency neurons showed only occasional brief pauses (Dodson et al , 2015; Mallet et al , 2016).…”
Section: Discussionmentioning
confidence: 64%
“…Many GPe neurons reportedly exhibit pauses in non-human primates 33,40 and humans 41 . Although pauses were not correlated with any movements, relationships with alertness, task engagement, and motor learning have been reported [42][43][44] . Hence, the probability of pauses depends upon the animal's state, while the timing of individual pauses does not have any physiologic significance.…”
Section: Discussionmentioning
confidence: 89%